Length-weight relationships of seven catfish species in peninsular Malaysia - Yusof, Muhammad Fitri; Siraj, Siti Shapor; Daud, Siti Khalijah (Academic Journals Inc., 2011)
The study described the Length-Weight Relationship (LWR) of commercially important and indigenous freshwater catfishes from Peninsular Malaysia. Seven species of freshwater catfishes from three families (Bagriidae, Clariidae and Pangasidae) were collected from various rivers in Peninsular Malaysia. Allometric coefficient, b in LWR varied between 2.19 and 3.20. The LWR with high correlation coefficient (r2) is significant for all species except P. nasutus. The present study also documented first reference for Pangasius nasutus and Pseudomystus siamensis.